Coral reef fish predator maintains olfactory acuity in degraded coral habitats - Natt, Michael (PLoS One, 2017)
Coral reefs around the world are rapidly degrading due to a range of environmental stressors. Habitat degradation modifies the sensory landscape within which predator-prey interactions occur, with implications for olfactory-mediated behaviours. Predator naïve settlement-stage damselfish rely on conspecific damage-released odours (i.e., alarm odours) to inform risk assessments. Yet, species such as the Ambon damselfish, Pomacentrus amboinensis, become unable to respond appropriately to these cues when living in dead-degraded coral habitats, leading to increased mortality through loss of vigilance. Reef fish predators also rely on odours from damaged prey to locate, assess prey quality and engage in prey-stealing, but it is unknown whether their responses are also modified by the change to dead-degraded coral habitats. Implications for prey clearly depend on how their predatory counterparts are affected, therefore the present study tested whether olfactory-mediated foraging responses in the dusky dottyback, Pseudochromis fuscus, a common predator of P. amboinensis, were similarly affected by coral degradation. A y-maze was used to measure the ability of Ps. fuscus to detect and move towards odours, against different background water sources. Ps. fuscus were exposed to damage-released odours from juvenile P. amboinensis, or a control cue of seawater, against a background of seawater treated with either healthy or dead-degraded hard coral. Predators exhibited an increased time allocation to the chambers of y-mazes injected with damage-released odours, with comparable levels of response in both healthy and dead-degraded coral treated waters. In control treatments, where damage-released odours were replaced with a control seawater cue, fish showed no increased preference for either chamber of the y-maze. Our results suggest that olfactory-mediated foraging behaviours may persist in Ps. fuscus within dead-degraded coral habitats. Ps. fuscus may consequently gain a sensory advantage over P. amboinensis, potentially altering the outcome of predator-prey interactions.